Analysis Of Factors And Performance Of Puskesmas In Tb Case Finding In Lhokseumawe City - yuziani yuziani; Annisa Uljannah; Harvina Sawitri; Mutia Maulina; Vera Novalia; Noviana Zara (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Tuberculosis is still a health problem in Indonesia and the world today. Aceh Province has the highest number of TB cases in Indonesia, and North Aceh district is the number one highest district in Aceh Province. One effort to reduce the morbidity rate caused by TB is TB case detection (Case Detection Rate/CDR) and the success rate of treatment. The high and low rates of TB case discovery are influenced by the performance of all managers of the TB disease control program (P2TB), which all related parties support. This research describes officers' performance finding tuberculosis cases at the Lhokseumawe City Health Center. This type of research is quantitative with a cross-sectional design. Samples were taken from the total population, namely all officers responsible for TB at community health centres in Lhokseumawe, totalling 15 officers. The results of this research showed that the dominant gender was 86.7% female officers, 80% D3 education level, 100% good knowledge, 86.7% sufficient motivation of officers, 73.3% good leadership of the head of the community health centre, 86% good training for TB officers, 7%, case detection was 100% good, work period was more than two years 73.3%, and the achievement of TB case discovery was only one health centre that reached the standard. The conclusion from research conducted at the Lhokseumawe City Health Center is that many factors influence officers' performance in case finding.